Care home residents who die in hospital: exploring factors, processes and experiences. (24th February 2020) - Alcorn, Gemma; Murray, Scott A; Hockley, Jo
Abstract: Background: Care home residents are increasingly frail with complex health and social care needs. Their transfer to hospital at the end-of-life can be associated with unwanted interventions and distress. However, hospitals do enable provision of care that some residents wish to receive. We aimed to explore the factors that influence hospital admission of care home residents who then died in hospital. Methods: This study combined in-depth case note review of care home residents dying in two Scottish teaching hospitals during a 6-month period and semi-structured interviews with a purposive sample of 26 care home staff and two relatives. Results: During the 6-month period, 109 care home residents died in hospital. Most admissions occurred out-of-hours (69%) and most were due to a sudden event or acute change in clinical condition (72%). Length of stay in hospital before death was short, with 42% of deaths occurring within 3 days. Anticipatory Care Planning (ACP) regarding hospital admission was documented in 44%. Care home staff wanted to care for residents who were dying; however, uncertain trajectories of decline, acute events, challenges of ACP, relationship with family and lack of external support impeded this. Conclusions: Managing acute changes on the background of uncertain trajectories is challenging in care homes. Enhanced support is required to improve and embed ACP in care homes and to provide rapid, 24 hours-a-day support to manage difficult symptoms and acute changes.